Pengembangan Komoditas Unggulan Tanaman Pangan di Kabupaten Bone - A Akbar; Baba Barus; Dwi Putro Tejo Baskoro (TATALOKA, 2014)
Crop farming sector is an important sector in Bone, but it’s productivity is still fluctuating. Currently commodities occur in the area, that may contribute to agriculture development, and they may distribute in unappropriate physical suitability and lack support of infrastructure. This study aims to (1) Identify the superior crop commodities in Bone, (2) Identify availability of  agricultural infrastructure and facilities, (3) Evaluate land suitability for food crops in Bone, (4) Develop guidelines for location and strategies for development of superior commodity crops  in Bone. The analytical method used is the LQ analysis, MCDM-TOPSIS, schallogram, land suitability, and A'WOT. Results showed that paddy, corn and soybeans are superior commodities. Suitable land for development are  20,7% for rice, 16,0% for corn and  0,9% for soybean. Location for development commodity is directed in district Libureng, Awangpone, Tellusiattinge, Ponre, Kahu, Lamuru, Cina, Salomekko, Ajangale, Tonra, Bontocani, Cenrana, Kajuara, Amali, Mare, Tellulimpoe dan Patimpeng.  Strategies development, namely: (a) Optimizing and utilizing the potential of the area/natural resources, human resources and government policies for the development of food crops selected; (b) Increasing partnerships between stakeholders; (c) Enhancing the ability of research institutions to develop new technologies, and (d) Utilizing a strategic position region business import export trade of agricultural products.